2003
DOI: 10.1167/iovs.02-1308
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Chemokine Expression in the Retinal Vasculature in Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion retinal injury results in generation of highly chemotactic agents, initially in the retinal vasculature, then in the other inner retinal layers. Such differential chemokine expression may play a role in leukocyte recruitment and selective leukocyte infiltration in the inner retina, leading to retinal damage primarily localized to the ganglion cells and other inner neuronal structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 26 publications
3
48
0
1
Order By: Relevance
“…Treatment with anti-CCL4/ MIP-1ß delayed onset and reduced duration of AAU (Adamus et al, 2001). The retinal ischemia-reperfusion model showed an upregulation of CCL4/MIP-1beta in the retinal vessels and these results confirm that this chemokine may be involved in the inflammatory element of pathogenesis of retinal neovascularization (Jo et al, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Treatment with anti-CCL4/ MIP-1ß delayed onset and reduced duration of AAU (Adamus et al, 2001). The retinal ischemia-reperfusion model showed an upregulation of CCL4/MIP-1beta in the retinal vessels and these results confirm that this chemokine may be involved in the inflammatory element of pathogenesis of retinal neovascularization (Jo et al, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, previous reports have shown that retinal ischaemia stimulates IL-8 and MCP-1 production, and both chemokines are involved in retinal neovascularization. [31][32][33][34] Although ischaemia as seen using FFA was one of the exclusion criteria, we cannot absolutely exclude that this was present in our patients. So retinal ischaemia may have also contributed to hyperproduction of IL-8 and MCP-1.…”
Section: Il-8 and Mcp-1 In Brvo Macular Oedemamentioning
confidence: 99%
“…2 MIP-1b was first isolated from the culture medium of LPS-activated macrophages, 3 and it recruited macrophages/microglia to the sites of injury in patients with arthritis, 4 sepsis, 5 and systemic sclerosis. 6 The upregulation of MIP-1b in the ischemic retina has been shown to occur in an ischemia-reperfusion injury model, 7 and its receptor, CCR5, is involved in the development of corneal NV. 8 However, it is not known what role the MIP-1b/CCR5 system has in the hypoxia-induced retinal NV.…”
mentioning
confidence: 99%